2013
DOI: 10.1007/s00167-013-2514-z
|View full text |Cite
|
Sign up to set email alerts
|

Functional bracing of ACL injuries: current state and future directions

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 88 publications
1
42
0
Order By: Relevance
“…In human medicine, knee braces are commonly used for multiple conditions (13)(14)(15)(16)(17)(18)(19). Bracing of the human knee has been shown to enhance proprioception/joint position sense, permit the injured limb to relax, reduce fatigue in injured limb, provide some mechanical protection against impact, and slow movement down to allow muscles time to react and control motion (14,(17)(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In human medicine, knee braces are commonly used for multiple conditions (13)(14)(15)(16)(17)(18)(19). Bracing of the human knee has been shown to enhance proprioception/joint position sense, permit the injured limb to relax, reduce fatigue in injured limb, provide some mechanical protection against impact, and slow movement down to allow muscles time to react and control motion (14,(17)(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…neutralizing cranial tibial thrust in the ACL deficient knee). One recent review reported that biomechanical evaluations of functional braces have been mixed and concluded further functional brace studies designed to apply forces to the knee joint similar in magnitude to the native ACL should be performed (16). In spite of this, functional knee braces are still thought to be effective in controlling anteroposterior translation in ACL-deficient knees under low loading conditions (17)(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the ligament is well vascularized, which is required for tissues healing [8, 9]. Different methods have been undertaken to enhance healing of the ACL, including primary suture repair, healing response techniques, immobilization, bracing, and supplementation with scaffolds, growth factors, and collagen-platelet composites [5, 1014]. Although primary ACL suture has been shown to improve laxity in the short term, it has shown a high failure rate with longer follow-up [5, 11, 14].…”
Section: Introductionmentioning
confidence: 99%
“…Although primary ACL suture has been shown to improve laxity in the short term, it has shown a high failure rate with longer follow-up [5, 11, 14]. Several functional knee braces have been evaluated and noted not to affect knee anterior laxity [10, 15, 16]. Fujimoto et al, however, showed in a group of 31 patients with low athletic demands that bracing with an extension block improved stability in 74% of patients, but 26% of the patients went on to require ACL reconstruction [17].…”
Section: Introductionmentioning
confidence: 99%